Dear Pictograph: Investigating the Role of Personalization and Immersion for Consuming and Enjoying Visualizations - Romat, Hugo; Henry Riche, Nathalie; Hurter, Christophe; Drucker, Steven; Amini, Fereshteh; Hinckley, Ken (CHI 2020, 2020)
Much of the visualization literature focuses on assessment of visual representations with regard to their effectiveness for understanding data. In the present work, we instead focus on making data visualization experiences more enjoyable, to foster deeper engagement with data. We investigate two strategies to make visualization experiences more enjoyable and engaging: personalization, and immersion. We selected pictographs (composed of multiple data glyphs) as this representation affords creative freedom, allowing people to craft symbolic or whimsical shapes of personal significance to represent data. We present the results of a qualitative study with 12 participants crafting pictographs using a large pen-enabled device and while immersed within a VR environment. Our results indicate that personalization and immersion both have positive impact on making visualizations more enjoyable experiences.
(to appear)